PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 163 PEKANBARU - Nofrita, Lisya; ', Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This study is based on the low learning outcomes social sciences of class IV SD Negeri 163 Pekanbaru. The KKM determined by the school is 73. Of the 40 students, only 16 students (40%) attained the KKM, while the students who had not reached the KKM were 24 students (60%) with an average grade is 62.3. This study is a Classroom Action Research (CAR) aimed to improve the learning outcomes social sciences class IV SD Negeri 163 Pekanbaru by applying the model of learning cooperative, examples non examples’ type. Activity teachers on the first cycle of the first meeting obtained 70.8% with well category, at the second meeting increased to 83.3% with well category too. Furthermore, second cycle of the first meeting of teacher’s activity also increased to 87,5% with very good category and second cycle at the second meeting increased to 91,7% with very good category too. While the activity of student in first cycle of first meeting get 66,7% with good category, at second meeting of first cycle increased to 79,16% with good category too. While in the first meeting of the second cycle of student activity increased to 83.3% with very good category and at the second meeting of second cycle increased to 87.5% with very good category. Learning result data obtained from the average basic score is 62.3 which is increased to 14% with an average is 71 on the first cycle. On the second cycle increased to 28.41% with an average is 80. In the basic score of social sciences learning classical completeness students are 40% (not complete). After applied model of cooperative learning examples non examples’ type in first cycle of classical completeness of learning student increase with classical completeness is 55% and in second cycle classical completeness learning student increase again with classical mastery is 87,5%.Keywords: Cooperative learning model examples non examples type, social sciences learning outcomes